Penerapan Symbolic Modeling melalui Pendekatan Asuhan Keperawatan Keluarga dalam Menurunkan Kejadian Cedera pada Anak Usia Sekolah - Utami, Ressa Andriyani; Setiawan, Agus; Fitriyani, Poppy (Sekolah Tinggi Ilmu Kesehatan RS Husada, 2018)
Abstract Injuries are global health threat because 7% of deaths are caused by injuries. The results of basic health research (2013) showed that the incidence of injuries that occurred at home as much as 36.5%. Behavioral factors that include knowledge, attitudes and skills of family and school-age children related to injury prevention affect the incidence of injury in school-aged children. Injury prevention strategy is done with the Symbol Model using video animation involving family. This study aims to provide an overview of the application of Model Sandi (Simbol Andi) in the prevention of injury to the family. The design of this study is a case study. The number of research samples are 10 families taken through purposive sampling technique. This research was conducted for 6 months. The results of the study showed that there was a change of knowledge, attitudes and skill of the family as well as the increasing of family independence level. Intervention Model Sandi is expected to be one of the approaches of family nursing interventions in solving the problem of risk of injury in school-aged children.